Astronomical Analysis of Hilal Testimony Data: A Comprehensive Study of the Ministry of Religious Affairs of the Republic of Indonesia from 1962 – 2021 - Sopwan, Novi; Alhamidi, Abu Dzarrin; Zulikrom, Muhammad Muadz; Humam, Muhammad Akbarul (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2024)
This study is a quantitative study of hilal position parameters in the report of the results of hilal testimony at the beginning of Ramadan, Shawwal, and Zulhijjah. A compilation of hilal testimony data from each Decree of the Minister of Religious Affairs of the Republic of Indonesia (KMA RI) from 1962 - 2021 was carried out. The position parameters, crucial for our analysis, were calculated with utmost precision for each hilal testimony data using the well-established and accurate VSOP87 and ELP91. There is a discrepancy between hilal testimony data and hilal visibility, which is used as a reference for hilal visibility. The results showed that all hilal testimony data is a hilal that is difficult to observe with the naked eye. Some testimonies show hilals that are impossible to detect. Another possibility is the presence of errors of observed objects other than hilal, such as a glowing cloud resembling the hilal, the appearance of the crescent of Venus that is suspected to be hilal, or the appearance of a lamp near the horizon that is identified as a suspected hilal. In the case of negative hilals that have been successfully observed, the possibility of miscalculation of the hilal position is also very high.